Abrasion resistance of ultra high performance concrete incorporating coarser aggregate. (20th March 2018) - Pyo, Sukhoon; Abate, Selamu Yihune; Kim, Hyeong-Ki
Highlights: UHPC shows excellent abrasion resistance compared with HPC. Abrasion resistance of UHPC was decreased by using coarser aggregates. Exposure of steel fiber might became surface corrosion spots. Abstract: This experimental study was conducted to evaluate the abrasion resistance of ultra high performance concrete (UHPC) that incorporated pre-selected coarser aggregates. The aggregates were selected based on their properties and local availability. In addition, coal bottom ash powder was also used with coarser aggregates as a replacement for silica powder. The examination was made according to the ASTM C 944 test method and the results were determined and presented as mass loss and depth of abrasion. All the results from the tests reveal the excellent abrasion resistance of UHPC; however, when compared to each other, the UHPC with coarser aggregates shows a lower abrasion resistance than the UHPC with no coarser aggregates.